Fotografar, fabular: a fotografia que acontecimentaliza a Revolta de 1924 - Carboni, Maria Cecília Conte (2018)
This research investigates how photography can transform historical events into happenings, and has as its object a case study of the photographs about the 1924 Revolt, held in São Paulo. Its intention is to speculate on another possible story that the photographs try to tell about the episode, understanding them as trails capable of proposing another narrative. It seeks to transgress the traditional concept of photography as a proof of reality, understood as objective and secure in the register of its referents. Another focus of extreme relevance to the thesis is the question of the constitution of reality constructed by photography, especially when this real context takes on a dimension of historical value. When you come across the photographs, you can see how much they fail to properly register the Revolt, after all, can the photography not record what it photographs? Faced with this question, others are possible, especially the doubt about the photographic record of the historical event. This is the starting point of the research and the main hypotheses raised by this question are: a) the photographic record is not the only element of the photograph; b) photography involves ambivalences that result in powers, capable of catching unsuspected realities in the photographed context; c) from ambivalence, it is possible to review the role of photography as a record and its influence on the arrangement of realities recorded and preserved as memories of time, resulting in photographic fable. In order to arrive at the idea of photographic fable, it was necessary to interface with the field of history, especially when dealing with the event and happening, as well as the trace, so we used a bibliography to support this approach, besides working empirically with the photographs collected in several collections, making the selection of the images, analyzing their narratives and then comparing the photographs, which should be able to identify the traces of those narratives and the possible history that build the facts, from and despite of them. The research is based on concepts and reflections brought by various authors associated with different research fronts that, mainly and at various moments, are associated with each other, through concepts, areas and themes. We emphasize François Dosse and Gilles Deleuze, Mauricio Lazzarato and Muniz Sodré in the discussions around the event, Carlo Ginzburg in the concept of trace, Walter Benjamin as an author who underlies the historical approach, and so many other historians who bring accounts about the time and the city . Authors such as Joan Fontcuberta and, once again, Benjamin, and especially Vilém Flusser, permeate discussions about photography, as well as references to the event of the 1924 Revolt, present in various books and authors. The thesis presents in the first chapter the political and cultural contextualization of the event, in addition to inserting it in the city of São Paulo and in the fragments of the military thought of the time, trying to propose a wide evental arch, even if initially, of photography. In order for the proposed arc to be erected, it is necessary to deconstruct the event, proposing to recognize it in another way. In the second chapter, the object of study is evidenced, bringing to the debate, besides the general nature of photography, the specificities of the photographs in question and their analyzes, identifying them as traces that contribute to different understandings about the Revolt. In the third chapter we will address the issue of the event and the co-ordinations established between this concept and the photographs under analysis, thus proposing the idea of photographic fable